Increased Ubqln2 expression causes neuron death in transgenic rats. (10th October 2016) - Huang, Bo; Wu, Qinxue; Zhou, Hongxia; Huang, Cao; Xia, Xu‐Gang
Abstract: Pathogenic mutation of ubiquilin 2 (UBQLN2) causes neurodegeneration in amyotrophic lateral sclerosis and frontotemporal lobar degeneration. How UBQLN2 mutations cause the diseases is not clear. While over‐expression of UBQLN2 with pathogenic mutation causes neuron death in rodent models, deletion of the Ubqln2 in rats has no effect on neuronal function. Previous findings in animal models suggest that UBQLN2 mutations cause the diseases mainly through a gain rather than a loss of functions. To examine whether the toxic gain in UBQLN2 mutation is related to the enhancement of UBQLN2 functions, we created new transgenic rats over‐expressing wild‐type human UBQLN2. Considering that human UBQLN2 may not function properly in the rat genome, we also created transgenic rats over‐expressing rat's own Ubqln2. When over‐expressed in rats, both human and rat wild‐type Ubqln2 caused neuronal death and spatial learning deficits, the pathologies that were indistinguishable from those observed in mutant UBQLN2 transgenic rats. Over‐expressed wild‐type UBQLN2 formed protein inclusions attracting the autophagy substrate sequestosome‐1 and the proteasome component 26S proteasome regulatory subunit 7. These findings suggest that excess UBQLN2 is toxic rather than protective to neurons and that the enhancement of UBQLN2 functions is involved in UBQLN2 pathogenesis. Pathogenic mutation in ubiquilin 2 (UBQLN2) causes neurodegeneration in ALS and FTLD. Studies in rodent models suggest a gain of toxic function in mutant UBQLN2. We created new transgenic rats as a relevant model and examined whether enhancing wild‐type UBQLN2 expression is implicated in the pathogenesis of mutant UBQLN2. We observed that over‐expression of human or rat wild‐type Ubqln2 caused protein aggregation and neuronal death in transgenic rats. Our findings suggest that excess UBQLN2 is toxic rather than protective to neurons and that uncontrolled enhancement of UBQLN2 function is involved in UBQLN2 pathogenesis. Read the Editorial Highlight for this article on page159 . Abstract : Pathogenic mutation in ubiquilin 2 (UBQLN2) causes neurodegeneration in ALS and FTLD. Studies in rodent models suggest a gain of toxic function in mutant UBQLN2. We created new transgenic rats as a relevant model and examined whether enhancing wild‐type UBQLN2 expression is implicated in the pathogenesis of mutant UBQLN2. We observed that over‐expression of human or rat wild‐type Ubqln2 caused protein aggregation and neuronal death in transgenic rats. Our findings suggest that excess UBQLN2 is toxic rather than protective to neurons and that uncontrolled enhancement of UBQLN2 function is involved in UBQLN2 pathogenesis. Read the Editorial Highlight for this article on page159 .